Influence of eating while watching TV on food preference and overweight/obesity among adolescents in China: a longitudinal study - Jinli Xian; Tingwei Ren; Ming Kuang (Frontiers Media S.A., 2024)
BackgroundEating while watching TV was found associated with unhealthy food preferences and obesity in adolescents in foreign studies, which is not clear in China. The study aims to explore the influence of eating while watching TV on food preferences and overweight/obesity in Chinese adolescents.MethodsData from 1768 adolescents (aged 12-17 years) in the 2006, 2009, 2011, and 2015 China Health and Nutrition Survey (CHNS) was analyzed. The height and weight were measured. Mixed effect models were used to identify the associations between eating while watching TV and adolescents' food preferences and overweight/obesity.ResultsAdolescents eating while watching TV ≥1 time/week were more likely to prefer fast food, salty snacks and soft drinks than those eating while watching TV <1 time/week. Adolescents eating meals while watching TV ≥1 time/week were less likely to prefer vegetables than those eating meals while watching TV <1 time/week. In addition, adolescents eating snacks while watching TV ≥1 time/week were more likely to be overweight/obesity than those eating meals while watching TV <1 time/week (odds ratio [OR] = 7.16; 95% confidence interval [CI] 1.39-36.93).ConclusionEating snacks while watching TV was positively associated with adolescents' unhealthy food preferences and overweight/obesity. Eating meals while watching TV was associated with adolescents' unhealthy food preferences. Implementing web-based Community-based participatory research (CBPR) about reducing eating while watching TV may be a practical strategy to develop healthy food preferences and prevent overweight/obesity in Chinese adolescents.